Long‐term uveal and capsular biocompatibility of a novel modular intraocular lens system. Issue 4 (25th January 2018) - Ludlow, Jason; Nguyen, Jason; Aliancy, Joah; Masino, Bryan; Ha, Larry; Werner, Liliana; Mamalis, Nick
Abstract: Background: We evaluated the long‐term biocompatibility and safety of a new modular posterior chamber intraocular lens (IOL) system in rabbit eyes. Methods: Seven New Zealand rabbits underwent bilateral phacoemulsification with placement of the modular IOL in OD and a control IOL (SA60AT) in OS. Slit‐lamp examinations were performed at postoperative weeks 1, 2, 3, 4, 6 and 8 and months 3 and 6. All rabbits were then sacrificed and eyes enucleated. The eyes were examined grossly from the Miyake–Apple view. Selected IOLs were explanted and underwent surface staining for implant cytology. All globes were then sectioned and processed for histopathological examination. Results: The modular IOL remained stable in all seven rabbits through the entire follow‐up period. Biocompatibility was better than the control lens at six months postoperatively, on account of less extensive synechiae formation as assessed by slit‐lamp examination. At the six‐week examination, posterior capsule opacification (PCO) was significantly better in the test group (scored as 1.71 ± 0.8 versus 3.28 ± 0.48 in the control group, p = 0.0008). On gross examination with the Miyake–Apple view, Soemmering's ring formation was significantly better in the test group, (5.14 ± 1.57 versus 10.85 ± 1.95 in the control group, p = 0.002). Conclusion: Previous studies showed that explantation/exchange of the modular system optic was safer and easier than with a standard IOL. The new modular IOL system has demonstrated better long‐term biocompatibility compared to the control lens at six months postoperatively in the rabbit model.